Justice : rights and wrongs - Wolterstorff, Nicholas (Princeton University Press, 2008)
Wide-ranging and ambitious, Justice combines moral philosophy and Christian ethics to develop an important theory of rights and of justice as grounded in rights. Nicholas Wolterstorff discusses what it is to have a right, and he locates rights in the respect due the worth of the rights-holder. After contending that socially-conferred rights require the existence of natural rights, he argues that no secular account of natural human rights is successful; he offers instead a theistic account. Wolterstorff prefaces his systematic account of justice as grounded in rights with an exploration of the.